2016
DOI: 10.3233/rnn-150563
|View full text |Cite
|
Sign up to set email alerts
|

Interactive virtual feedback improves gait motor imagery after spinal cord injury: An exploratory study

Abstract: Purpose: Motor imagery can improve motor function and reduce pain. This is relevant to individuals with spinal cord injury (SCI) in whom motor dysfunction and neuropathic pain are prevalent. However, therapy efficacy could be dependent on motor imagery ability, and a clear understanding of how motor imagery might be facilitated is currently lacking. Thus, the aim of the present study was to assess the immediate effects of interactive virtual feedback on motor imagery performance after SCI.Methods: Nine individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…The MD&B score was 17/27 for both studies indicating low risk of bias. The third study evaluated twosessions of 1.5 hours (≥1 hour apart) of a VR environment projected onto two screens in front of patients with a spinal cord injury (C4 or lower) at least 3 months prior 49. This study found no significant difference in pain reported immediately after the VR exposure.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The MD&B score was 17/27 for both studies indicating low risk of bias. The third study evaluated twosessions of 1.5 hours (≥1 hour apart) of a VR environment projected onto two screens in front of patients with a spinal cord injury (C4 or lower) at least 3 months prior 49. This study found no significant difference in pain reported immediately after the VR exposure.…”
Section: Resultsmentioning
confidence: 96%
“…While the HMD was more effective in reducing subjective pain ratings, mobile devices also were able to achieve pain reduction effectively. The Visual Analog Pain Scale decreased when subjects were using the mobile phone pain distraction (mean scoredecreased by 0.58, p < 0.02), while it decreased by an additional 0.445 (p < 0.04) when the HMD was used.Pain intensity during treatmentunable to calculateunable to calculateunable to calculateunable to calculateRoosink, 201649Quasi-experimental study (no comparison group)9Range: 25-72A convenience sample was recruited among the outpatients of the Institut de r'eadaptation en d´eficience physique de Qu´ebec (IRDPQ). Individuals had sustained a traumatic SCI at least 3 months prior to participation, and had a lesion at the level of C4 or lower.NPChronicMD&B 17/27The set-up consisted of an inertial movement sensor, a virtual reality system, two projectors (allowing for 3D vision), and a large silver-coated projection screen.Patients engaged in a virtual forest path leading to the door of a small cabin (fixed distance) with a horizontal progress bar in the lower left corner of the screen (to provide feedback on the distance covered).…”
Section: Resultsmentioning
confidence: 99%
“…However, long-term effects of MI training probably help to overcome these experienced troubles, as has been suggested by Gustin et al ( 2008 ). Furthermore, it is important to note, that this does not mean that the ability to perform MI is impaired, as it has been reported that MI vividness in patients with SCI is comparable to that of healthy subjects (Hotz-Boendermaker et al, 2008 ; Di Rienzo et al, 2014b , c , 2015 ; Fusco et al, 2016 ; Roosink et al, 2016 ). Additionally, we investigated visual and kinesthetic MI and it is possible that MI strategies may change after SCI (Fiori et al, 2014 ).…”
Section: Discussionmentioning
confidence: 96%
“…Virtual reality (VR) technology, as an emerging intervention, has gradually become an adjunctive therapy of various diseases (such as cerebral palsy, depression, and Parkinson's disease) (Roosink et al, 2016 ). VR technology is a technology that uses the human senses (sight, touch, movement) to control a virtually-created environment.…”
Section: Introductionmentioning
confidence: 99%